Physical Fitness and Dietary Intake Improve Mental Health in Chinese Adolescence Aged 12–13 - Liang, Wenjie; Fu, Jian; Tian, Xin; Tian, Jiaxue; Yang, Yu; Fan, Wencui; Du, Zijuan; Jin, Zheyu (Frontiers in Integrative Neuroscience, 2022)
Abstract: Objective: The study aims to provide theoretical basis for promoting adolescent healthy lifestyle and preventing mental problems by exploring the relationship between physical fitness, calcium intake, calorie intake and adolescent mental health. Methods: We selected 253 adolescents aged 12-13 from three middle schools in Central Jiangsu Province. T-test and analysis of variance were used to analyze the differences of variables between different genders and body mass index, and Pearson correlation and stepwise multiple regression were used to explore the relationship between physical fitness, dietary intake and mental health. Results: The height (165.13 ± 8.07), weight (55.24 ± 13.00) and strength quality (64.93 ± 21.66) of boys are higher than those of girls (161.67 ± 6.44,48.99 ± 8.97,58.40 ± 23.75, P < 0.05), and the flexibility quality (74.59 ± 14.75) of girls is higher than that of boys (68.30 ± 20.84) (P < 0.05). There were significant differences in the total scores of speed and physical fitness (F values were 4.02187.73, 3.07, 5.95, 10.33 and 9.52, respectively, P< 0.05). There is a significant positive correlation between calcium intake, cardiopulmonary fitness and mental health (r = 0.276, P < 0.01; r = 0.159, P < 0.05). Calcium intake and cardiopulmonary fitness could explain 8.4% of the changes in mental health of adolescents aged 12-13（Δ R2=0.084,P＜0.05）. Conclusion: Calcium intake and cardiopulmonary fitness in adolescence are extremely important, and they have the potential to change mental health in the whole life process. Adequate calcium intake and the improvement of cardiopulmonary fitness in adolescents aged 12-13 are essential for the good development of their mental health.